Monitoring distribution systems for Legionella pneumophila using Legiolert. Issue 1 (24th January 2019) - LeChevallier, Mark W.
Abstract : This study implemented the Legiolert test (a culture‐based assay for L. pneumophila based on the most probable number [MPN]) at 12 utilities to assess their experiences and to develop a baseline of Legionella pneumophila occurrence in drinking water distribution systems. A total of 679 samples were analyzed during the study: 53 source water, 50 from the plant effluent, and 576 from the distribution system. L. pneumophila was detected in three of five source water samples at one utility but was not detected in any of the treated plant effluent samples. L. pneumophila was detected in only one distribution sample (0.17%) at a concentration of 1 MPN/100 mL in a sample that contained 0.72 mg/L free chlorine and was serotyped as belonging to the 2–14 serogroup. Four (0.7%) distribution samples could not be confirmed by serotyping. Overall, the utilities found the test easy to learn and apply in their systems. This study provides a precedent for future monitoring of drinking water systems.